2019
DOI: 10.1111/bph.14597
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of sphingosine‐1‐phosphate receptor 2 attenuates allergic asthma in mice

Abstract: Background and Purpose: Sphingosine-1-phosphate 2 (S1P 2 ) receptors have been implicated in degranulation of mast cells. However, functions of S1P 2 receptors have not been investigated in an in vivo model of allergic asthma.Experimental Approach: Using an ovalbumin (OVA)-induced asthma model, the function of S1P 2 receptors was evaluated in S1P 2 -deficient mice or in mice treated with JTE-013, a selective S1P 2 antagonist. Bone marrow-derived dendritic cells (BMDCs) were used to investigate the roles of S1P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 50 publications
(57 reference statements)
1
25
0
Order By: Relevance
“…Furthermore, topical application could avoid the possible side effects of systemic JTE-013 administration. In addition, this study supports the previous finding of pro-allergic functions of S1P 2 ( Park and Im, 2019a ) and also pro-inflammatory functions of S1P 2 ( Park and Im, 2019b ). Therefore, this finding proves a new direction for S1P 2 receptor therapeutics.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, topical application could avoid the possible side effects of systemic JTE-013 administration. In addition, this study supports the previous finding of pro-allergic functions of S1P 2 ( Park and Im, 2019a ) and also pro-inflammatory functions of S1P 2 ( Park and Im, 2019b ). Therefore, this finding proves a new direction for S1P 2 receptor therapeutics.…”
Section: Discussionsupporting
confidence: 92%
“…The in vivo anti-atopic effects of topical JTE-013 treatment may be caused by the inhibition of S1P 2 in mast cells and dendritic cells ( Oskeritzian et al ., 2010 ; Japtok et al ., 2012 ; Olivera et al ., 2013 ; Bock et al ., 2016 ; Park and Im, 2019a ), because S1P 2 has been proven to function as an activator of mast cell degranulation and dendritic cell maturation and migration ( Prieschl et al ., 1999 ; Oskeritzian et al ., 2010 ; Park and Im, 2019a ). However, the inhibition of S1P 2 in other cell types such as keratinocytes also could contribute to the effect of JTE-013 ( Kim et al ., 2004 ; Jeong et al ., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Study by Schulke et al showed that the fusion protein of flagellin A and OVA suppressed the Th2 response and prevented murine intestinal allergy when administrated during or before sensitization (Schulke et al, 2011). Park et al also investigated the effect of a sphingosine-1-phosphate 2 antagonist on allergic asthma in mice when treated during or before sensitization (Park & Im, 2019). In this context, we mainly studied the effect of S. pneumoniae aminopeptidase N (PepN) on allergic asthma when administrated during OVA sensitization and its mechanism and we also performed a model of prophylactic administration of PepN to further confirmed the protective effect of PepN on allergic asthma.…”
Section: Pepn Impaired Cd11b + Dendritic Cells-related Chemokines Pmentioning
confidence: 99%